Surface modification of aluminium alloy series 6 (AA6061 T657) and its corrosion characteristics / Christopher Tseu Zia Chyuan - Christopher Tseu, Zia Chyuan (2019)
Aluminium (Al) casting alloys are important materials for the fabrication of engine components such as engine block, cylinder head and piston rings. In the present study, a self-organized nanostructured Al2O3 layer on AA6061 T657 series was fabricated by anodization followed by heat treatment at 450 °C for 1.5 h. The microstructural features and surface wettability were explored. In addition, mechanical and corrosion behavior of Al2O3 nanoporous after anodizing and annealing were investigated. From the microstructural point of view, the average length and diameter of the optimized nanoporous arrays ranged from 0.5 μm and 25 nm. The adhesion results showed that the adhesion strength of coating increased for un-treated substrate from 1532 mN to annealed sample of 2240 mN. To improve the hardness of Al, heat treatment was carried out at 450 °C for 1 hour which returned with a hardness value of 71.2 as compared to substrate at 45.9. Besides, the annealed coating showed that highest wettability (lowest contact angle value). The results of corrosion tests in artificial sea water (ASW) showed that the corrosion rate values significantly decreased after anodization and subsequent annealing compared to the substrate